Can intergenerational equity be operationalized? - William R. Zame (Theoretical Economics, 2007)
A long Utilitarian tradition has the ideal of equal regard for all individuals, both those now living and those yet to be born. The literature formalizes this ideal as asking for a preference relation on the space of infinite utility streams that is complete, transitive, invariant to finite permutations, and respects the Pareto ordering; an ethical preference relation, for short. This paper argues that operationalizing this ideal is problematic. Most simply, every ethical preference relation has the property that almost all (in the sense of outer measure) pairs of utility streams are indifferent. Even if we abandon completeness and respect for the Pareto ordering, every irreflexive preference relation that is invariant to finite permutations has the property that almost all pairs of utility streams are incomparable (not strictly ranked). Moreover, no ethical preference relation can be measurable. As a consequence, the existence of an ethical preference relation is independent of the axioms used in almost all of formal economics and all of classical analysis. Finally, even if an ethical preference relation exists, it cannot be "explicitly described." These results have implications for game theory, for macroeconomics, and for economic development.
Keywords: D60; D70; D90; 330; Intergenerational equity; infinite utility streams; long run averages; overtaking criterion; Utilitarianism